2b-2=2b-2

Simple and best practice solution for 2b-2=2b-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2b-2=2b-2 equation:


Simplifying
2b + -2 = 2b + -2

Reorder the terms:
-2 + 2b = 2b + -2

Reorder the terms:
-2 + 2b = -2 + 2b

Add '2' to each side of the equation.
-2 + 2 + 2b = -2 + 2 + 2b

Combine like terms: -2 + 2 = 0
0 + 2b = -2 + 2 + 2b
2b = -2 + 2 + 2b

Combine like terms: -2 + 2 = 0
2b = 0 + 2b
2b = 2b

Add '-2b' to each side of the equation.
2b + -2b = 2b + -2b

Combine like terms: 2b + -2b = 0
0 = 2b + -2b

Combine like terms: 2b + -2b = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 1/6(x+6)=1/12(2x+12) | | 22y^4-33y^2+11y= | | 3(n+6)=9 | | 3x-3=18+8x | | 6(4x-4)=2(12x+1) | | y(y-6)=0 | | 5y^2=3y-7 | | 2b-3=2b-7 | | 27=p | | -4(6x-2)+3=-24x+11 | | 27=x | | 5-3(-4)=-7 | | 5=3b-8b | | 10.7=-d+43 | | 11x+4=5(2x-1)+9 | | 13-r=-3(-r+1) | | -3(4x+3)=-9 | | 2b-3=2b-6 | | 2a+3(a+4)= | | 8(x+2)-8=17-3x-9+11x | | 60t^4-4at^2+12t= | | (2x-3)(4x-2)= | | 0.33333333333x+10=55 | | x=2x^2+7x+9 | | -a/25=8 | | -4+9(x-2)=16x+3-7x | | .45x+.05(14-x)=.10(-25) | | -8-11=-5x+23 | | 0.80.2=x | | q^2+q-20=0 | | -(6xy-12)+3(5xy+8)= | | (6x+5)-1.3=-1.9 |

Equations solver categories